IoT Sea Level Monitoring: A Study on the Development and Field Testing - Kusuma, Hollanda Arief; Akbar, Muhammad Aris; Suhendra, Tonny (Jurnal Segara, 2024)
The measurement of sea level is important in oceanography, as it provides critical information about the ocean environment, including tides, currents, and water temperature. This study aimed to develop an IoT-based sea level monitoring device that can accurately measure sea level and transmit the data in real time. The device consisted of various components: an ESP32 Microcontroller, a GSM Module, an MS5803-14BA sensor, and a battery. The components were assembled on a PCB board and placed inside a waterproof box to protect the electronics from the ocean environment. The field test was conducted for 17 hours at the Tanjungpinang Class 1 Navigation Office Port, and the data was monitored through the Ubidots platform. The results showed that the device accurately measured sea level, with an RMSE value of 0.69 cm and an accuracy rate of 99.47%. However, the field test also revealed data transmission issues, with 18.81% of the data not being sent to the server. This low data transmission rate may have been due to low RSSI levels and issues with operator signal quality. Further research is needed to understand the reasons behind these data losses and to improve the device's overall performance. This study demonstrated the feasibility of using an IoT-based sea level monitoring device to accurately measure sea level and transmit the data in real time. It provides valuable information for further development and improvement of sea level monitoring systems.